A GENETIC ALGORITHM FOR THE INTEGRATED WAREHOUSE LOCATION, ALLOCATION AND VEHICLE ROUTING PROBLEM IN A POOLED TRANSPORTATION SYSTEM - Mrad, Mehdi; Bamatraf, Khaled; Alkahtani, Mohamed; Hidri, Lotfi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In this paper, we address the integrated location, allocation, and routing problem in the framework of a pooled transportation system. We assume that many enterprises with familiar customers aim to share their logistical means. Two collaborative scenarios are proposed and solved. A genetic algorithm based on Clarke and Wright’s savings heuristic is proposed to solve the different considered scenarios. A comparison is established between collaborative and noncollaborative scenarios to assess the impact of the proposed pooled transportation system. The obtained computational results indicate that the collaborative scenarios outperform the noncollaborative scenario. The total annual transportation cost is reduced by approximately 28% to 54% in the collaborative scenarios. Furthermore, the collaborative scenarios may reduce the number of required vehicles and increase the average fill rate of the used vehicles. It is worth noting that the proposed genetic algorithm solves efficiently adapted benchmark instances from the literature.